Financial Performance Analysis of Energy Companies Using Multi-Criteria Decision-Making Techniques: An Application in the BIST Electricity, Gas and Water Sector - Kahramani Koc, Azize; Tazegul, Alper; Durmus, Savas (International Journal of Economics and Financial Issues, 2024)
Energy plays a vital role in the macroeconomic development of countries. The increase in energy consumption and the increase in the number of energy companies are among the basic dynamics of country development and growth. Enhancing the financial performance of companies operating in the energy sector strengthens the competitive power of countries at both national and international levels. In this context, this study aims to determine the financial performance rankings of companies operating in the energy sector in Turkey over a 10-year period, identifying the most successful and least successful periods over the years. Using data from energy sector companies listed on Borsa Istanbul (BIST) between 2013 and 2022, after determining the research criteria, the weights of these criteria were calculated using the Entropy method. Subsequently, considering the criteria weights, the performance rankings of energy companies were determined year by year using the MAIRCA method. According to the results of the Entropy analysis, when the importance level is evaluated, the most significant criterion in 2013 was the Liquidity Ratio (LR), in 2014, 2017, 2018, and 2019 it was the Gross Profit Growth (GPG) criterion, in 2015 it was the Current Ratio (CR) criterion, in 2016 and 2022 it was the Net Profit Growth (NPG) criterion, and in 2020 it was the Net Profit Growth (NPG) criterion. Finally, in 2021, the most important criterion was determined to be EBITDA Growth (EBG). Furthermore, based on the MAIRCA analysis, the reasons behind the most successful and least successful years of the companies were explained using financial and activity reports, as well as special situation disclosure notifications obtained from the Public Disclosure Platform (PDP).